Metformin in adults with type 1 diabetes: Design and methods of REducing with MetfOrmin Vascular Adverse Lesions (REMOVAL): An international multicentre trial. Issue 4 (17th February 2017) - Petrie, John R.; Chaturvedi, Nish; Ford, Ian; Hramiak, Irene; Hughes, Alun D.; Jenkins, Alicia J.; E. Klein, Barbara; Klein, Ron; Ooi, Teik Chye; Rossing, Peter; Sattar, Naveed; Stehouwer, Coen D. A.; et al.
Abstract : Aims: Cardiovascular (CV) disease is a major cause of reduced life expectancy in type 1 diabetes (T1D). Intensive insulin therapy prevents CV complications but is constrained by hypoglycaemia and weight gain. Adjunct metformin reduces insulin dose requirement and stabilizes weight but there are no data on its cardiovascular effects. We have therefore initiated an international double‐blind, randomized, placebo‐controlled trial (REMOVAL: REducing with MetfOrmin Vascular Adverse Lesions in type 1 diabetes) to examine whether metformin reduces progression of atherosclerosis in adults with T1D. Individuals ≥40 years of age with T1D for ≥5 years are eligible if they have ≥3 of 10 specified CV risk factors. The enrolment target is 500 participants in 17 international centres. Materials and methods: After 12 weeks of single‐blind placebo‐controlled run‐in, participants with ≥ 70% adherence are randomized to metformin or matching placebo for 3 years with insulin titrated towards HbA1c 7.0% (53 mmol/mol). The primary endpoint is progression of averaged mean far wall common carotid intima‐media thickness (cIMT) measured by ultrasonography at baseline, 12, 24 and 36 months. This design provides 90% power to detect a mean difference of 0.0167 mm in cIMT progression between treatment arms (α = 0.05), assuming that up to 20% withdraw or discontinue treatment. Other endpoints include HbA1c, weight, LDL cholesterol, insulin requirement, progression of retinopathy, endothelial function and frequency of hypoglycaemia. Conclusion: REMOVAL is the largest clinical trial of adjunct metformin therapy in T1D to date and will provide clinically meaningful information on its potential to impact CV disease and other complications.